Discontinuation of teriflunomide and dimethyl fumarate in a large Italian multicentre population: a 24-month real-world experience - D’Amico, E.; Zanghì, A.; Sciandra, M.; Borriello, G.; Callari, G.; Gallo, A.; Salemi, G.; Cottone, S.; Buccafusca, M.; Valentino, P.; Bossio, R. B.; Grimaldi, L. M. E.; et al. (Journal of neurology, 2019)
Background Teriflunomide (TRF) and Dimethyl fumarate (DMF) are licensed drugs for relapsing-remitting Multiple Sclerosis (RRMS). Objectives We aimed to compare the rate and the time to discontinuation among persons with RRMS (pwRRMS), newly treated with TRF and DMF. Materials and methods A retrospective study on prospectively collected data was performed in nine tertiary MS centers, in Italy. The 24-month discontinuation rate in the two cohorts was the primary study outcome. We also assessed the time to discontinuation and reasons of therapy withdrawn. Discontinuation of TRF and DMF was defined as a gap of treatment ≥ 60 days. Results A cohort of 903 pwRRMS (316 on TRF and 587 on DMF) was analyzed. During 24 months of follow-up, pwRRMS on TRF and DMF showed similar discontinuation rates. The analysis of predictors with Cox regression model showed differences between the two groups ( p for log-rank test = 0.007); male gender [HR 2.21 (1.00–4.90); p = 0.01] and the number of previous switches [HR 1.47 (1.16–1.86); p = 0.01] were associated with higher hazard of discontinuation in the DMF group. Conclusions In a real-world setting, pwRRMS on TRF and DMF had similar discontinuation rates over 24 months. Male pwRRMS on DMF with a previous history of therapeutic failure are at more risk of discontinuation therapy.